Neoadjuvant chemotherapy with or without metformin in early-stage or locally advanced (non-metastatic) triple negative breast cancer—an open-label phase 2 randomized controlled trial - Ramani, Vinod K.; Basavalinga Sadashivaiah, Ajaikumar; Naik, Radheshyam (Frontiers in Oncology, 2025)
BackgroundTriple negative breast cancer (TNBC) is more prevalent among the younger age group and is the most aggressive form. Women with TNBC phenotype have 19% lower 5-year overall survival and 18% lower disease-free survival than their non-TNBC counterparts (1). Hence, extensive research is essential for the development of treatment modalities with high efficacy. Metformin is a widely used anti-diabetic drug. The research work has potential implications for re-purposing metformin in the clinical management of TNBC.MethodsThe study design includes a phase 2 randomized clinical trial of TNBC, with metformin given for the intervention arm and placebo oral tablet for the non-intervention arm. A total of 418 breast cancer patients are randomized with a parallel assignment model (209 each for the intervention and the control arms). This is an open-label trial where the primary purpose is treatment and adheres to the SPIRIT reporting guidelines. The trial will be initiated during January 2025 and is expected to be completed by May 2027.DiscussionThe clinical benefit, pathological response rate, and radiological response will be measured after 4.5 to 6 months of initiating treatment. The study will assess the recurrence-free survival (at intervals of 6 months) and overall survival at 2 years from treatment initiation. Patients who respond to the intervention are expected to have >50% decrease in the size of the primary tumor without the appearance of new lesions. RECIST v1.1 criteria are used to determine the objective tumor response for target lesions.